ANALYSIS OF CUSTOMER LOYALTY THROUGH THE FAST RESTAURANT CUSTOMER SATISFACTION FACTOR - Djumarno, Djumarno; Djamaluddin, Said; Hudaya, Agung; Djoko Setyo Widodo (Dinasti Publisher, 2020)
Economic growth and the growth of restaurant activities is very rapid, will affect many aspects of the economy, the need for staples, and other needs make distribution of merchandise will be increasingly busy. Business people will create strategies to complement the needs of the community or consumers. Nowadays, restaurant business is a solution for entrepreneurs, because the busyness of the community will make them prefer the meaning of fast food. Consumers will see the quality of products from the retail store they will buy, as well as the quality of service, whether the brand image displayed by fast food restaurants is in accordance with customer satisfaction. It is expected that loyalty will arise if satisfaction arises in the minds of these consumers. Data analysis techniques used are correlation analysis techniques and SEM (structural equation model) analysis techniques. Correlation analysis techniques to determine the relationship between variables, while SEM analysis techniques to determine how much influence the independent variable has on the dependent variable. The software used to process and analyze data from this study is Smart PLS version 3.0.